2022
DOI: 10.1080/15592324.2022.2064072
|View full text |Cite
|
Sign up to set email alerts
|

Combined interactions of amino acids and organic acids in heavy metal binding in plants

Abstract: This research focused on the different approaches to the transport and internal chelation of metals with amino acids and organic acids in plants. Therefore, in the first phase, the plants studied were identified the characteristics of the bioaccumulation factors. Steria pumila, Echium angustifolium, Typha angustifolia, Sisymbrium austriacum were identified as hyperaccumulators (Cd, Ni), accumulators (Pb, Sn, and Se), excluders (Cr, Hg). On the other hand, the Sisymbrium austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Heavy metals can form complexes with organic acids, resulting in changes in their toxicity and migration ability [43]. Previous studies have shown that the formation of strong bonds between chelating metals and carboxylate groups and phenolic hydroxide groups of organic acids plays an important role in metal accumulation and detoxification in plants [44,45]. Among organic acids, oxalate is a strong dicarboxylic acid anion and a good complexing agent for the binding of heavy metal cations [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals can form complexes with organic acids, resulting in changes in their toxicity and migration ability [43]. Previous studies have shown that the formation of strong bonds between chelating metals and carboxylate groups and phenolic hydroxide groups of organic acids plays an important role in metal accumulation and detoxification in plants [44,45]. Among organic acids, oxalate is a strong dicarboxylic acid anion and a good complexing agent for the binding of heavy metal cations [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the number of differential metabolites of Trichoderma Ts1 increased with the increase in the nuclide concentration, and the differential metabolites of organic acids and derivatives and of organic oxygen compounds increased signi cantly. Studies have shown that organic acids can reduce the available state of soil heavy metals and chelate heavy metals in organisms (Kocaman 2022;Zhao et al 2022). The data from this study indicated that the amino acid and carbohydrate metabolic pathways of Trichoderma Ts1 were altered.…”
Section: Discussionmentioning
confidence: 63%
“…The accumulation of organic and amino acids can chelate heavy metal ions and scavenge reactive oxygen species (ROS), thereby reducing intracellular oxidative damage [21]. Heavy metals can be chelated with low molecular weight organic acids stored in vacuoles and transformed into low or non-toxic chelating states, signi cantly contributing to plant heavy metal stress resistance [47,48]. For example, citric acid can alleviate Cd stress by reducing plants' Cd uptake [24].…”
Section: Role Of Organic Acids Under CD Stressmentioning
confidence: 99%
“…Plants adapt to abiotic stress by regulating self-metabolism; consequently, amino acids, fatty acids, and organic acids have been extensively studied [19][20][21]. Plants regulate the metabolic process of amino acids, organic acids, and fatty acids to cope with heavy metal toxicity; these metabolites vary with the plant variety or genotype [22,23].…”
mentioning
confidence: 99%